2020
DOI: 10.1002/ese3.648
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and application of airflow permeability characteristics of gob in roof cutting and pressure releasing mining method

Abstract: Cutting roof and release pressure technology has changed the pressure transmission mode of the roof and the caving characteristics of roof rock, which in turn has changed the permeability evolution of the gob. To obtain the permeability characteristics of the gob for the roof cutting and pressure releasing mining method, a mathematical model for the gob voidage and permeability was established by analyzing the overlying strata movement law and the lateral stress variation in the gob. The airflow migration law … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The specific distribution distance is shown in Figure 16 . 43 The study found that the goaf under the roof cutting and pressure releasing Y-type ventilation mode has a significantly larger range of influence than the traditional longwall mining oxidation heating zone, which greatly increases the possibility of coal spontaneous combustion. Combined with the research in this paper, it can be analyzed that the CO slow rising area is in the scattered tropical zone of the goaf spontaneous combustion zone.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The specific distribution distance is shown in Figure 16 . 43 The study found that the goaf under the roof cutting and pressure releasing Y-type ventilation mode has a significantly larger range of influence than the traditional longwall mining oxidation heating zone, which greatly increases the possibility of coal spontaneous combustion. Combined with the research in this paper, it can be analyzed that the CO slow rising area is in the scattered tropical zone of the goaf spontaneous combustion zone.…”
Section: Resultsmentioning
confidence: 97%
“…Chen determined the specific length of the three spontaneous combustion zones in the goaf under the traditional longwall mining mode and the roof cutting and pressure releasing mining mode based on the O 2 concentration through field measurement. The specific distribution distance is shown in Figure . The study found that the goaf under the roof cutting and pressure releasing Y-type ventilation mode has a significantly larger range of influence than the traditional longwall mining oxidation heating zone, which greatly increases the possibility of coal spontaneous combustion.…”
Section: Resultsmentioning
confidence: 97%
“…The void characteristics of fractured coal rocks are the key parameters affecting the volume and path of air leakage. 10,[47][48][49][50] Therefore, there is a relationship between the void fraction and the bulking factor of fractured coal rocks in a gob:…”
Section: Thermal Field Modelmentioning
confidence: 99%
“…Air leakage in a gob supplies oxygen to the residual coal while taking away the heat generated by oxidation. The void characteristics of fractured coal rocks are the key parameters affecting the volume and path of air leakage 10,47‐50 . Therefore, there is a relationship between the void fraction and the bulking factor of fractured coal rocks in a gob: γ=11Kpwhere K p is the bulking factor of the fractured coal rocks.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Zhang et al 23 conducted FLUENT numerical simulation of the dust distribution on the footway in the goaf. Chen et al 24 used FLUENT software to study the law of air movement in the return air roadway. Zhou et al 25 used FLUENT software to study the distribution of various gases in the goaf.…”
Section: Introductionmentioning
confidence: 99%